Pengaruh Kegiatan Menempel Gambar Dengan Teknik Mozaik Terhadap Perkembangan Motorik Halus Anak TK Kelompok B Di TK Pertiwi IV Banaran Sambungmacan Sragen Tahun Ajaran 2015/2016 - Widayati, Sholikha Desiana, Dra. Surtikanti, S.H., M.Pd, Wili Astuti, M. Hum (2016)
The purpose of this research is to know the influence of sticking pictures with the mosaic technique to the development of kindergarten fine motor Group B in TK Pertiwi IV Banaran Sambungmacan Sragen academic year 2015/2016. This research is a research experiment with type One Group Pretest - Posttest Design. The subject of this research is the son of Group B TK Pertiwi IV Banaran totalling 17. As for the data collection techniques in the research ares observation, whereas its data analysis techniques using descriptive analysis and inferensial analysis. Descriptive analysis is used to find out the fine motor development of children before and after the given experiment while inferensial analysis to test the hypothesis test using SPSS program T 16.0 for windows ie paired sample t-test. Based on the analysis of the results of research using the t-test is obtained a value retrieved value of tcount = 10.431 and ttable = 1,75 with probability 0.00. The probability of 0.00 ˂ɑ = 0.05 then null hypothesis (Ho) rejected, which that means there is the influence of sticking pictures with mosaic technique to the development of kindergarten fine motor Group B in TK Pertiwi IV Banaran Sambungmacan Sragen academic year 2015/2016.